Parotitis as an Initial Symptom of Kawasaki Disease - Koji Yokoyama (Case Reports in Pediatrics)
We report the case of a 13-month-old boy who developed right side parotitis as a first symptom of Kawasaki disease (KD). The data presented herein suggest that physicians should be aware that nonsuppurative parotitis is a possible manifestation of KD.